New Dihydroxytyrosyl Esters from Dicarboxylic Acids: Synthesis and Evaluation of the Antioxidant Activity In Vitro (ABTS) and in Cell-Cultures (DCF Assay) - Roma, Elia (Molecules, 2020)
New dihydroxytyrosyl esters 2a, 2c–2j of dicarboxylic acids were synthesized from methyl orthoformate protected hydroxytyrosol 3 and diacyl chlorides. New compounds were characterized (HRMS, FT-IR, (1)H- and (13)C-NMR), and tested for antioxidant activity both in vitro (ABTS) and on L6 myoblasts and THP1 leukemic monocytes cell culture by DCF assay. According to the ABTS assay, compounds 2a, 2c–2j showed a TEAC value of antioxidant capacity up to twice that of Trolox. Very high or complete ROS protections were obtained in the cell environment where lipophilicity and rigidity of dicarboxylic structure seem to facilitate the antioxidant effect. MTT assay and proliferation test were used for assessment of cell viability. These compounds can be envisaged as a new class of preservatives for food or cosmetic products.